AN ANALYSIS OF DEIXIS AND ITS REFERENCE USED BY MAIN CHARACTER IN “A THOUSAND WORDS” MOVIE SCRIPTBY STEVE KOREN - Raty Sasmita; Mei Hardiah; Elfrida . (Universitas Bengkulu, 2018)
The type of this research is Descriptive Qualitative research. It is aimed to find out the types of Personal, Time, Place, Discourse and Social Deixis and its reference by the main character in “A Thousand Words” movie script based on the theory that proposed by Levinson. The object of this study is “A Thousand Words” movie script by Steve Koren. This research found the five types of deixis in a movie script, they are person deixis (515 occurrences), time deixis (20 occurrences), place deixis (34 occurrences), discourse deixis (104 occurrences) and social deixis (1 occurrence). Besides that, the references found in this research were in person deixis were I, Me, We, Us, My as first person deixis; You, Your as second person deixis; He, She, It, They, Them, Him, Her as third person deixis which belongs to personal deixis (149 utterances); time deixis found were Now, Today, On a Tuesday, Three days, Two days, Then (19 utterances); place deixis found was Here, There, In (22 utterances); discourse deixis found was This, That, Those, These (60 utterances); ands the last, social deixis found were Mr (1 utterance).